BaEV-pseudotyped lentiviral vectors enable stable CAR expression and cytotoxic function in NK cells - Minji Park; Yuree Lim; Yujung Jo; Dong-Hyeon Jo; Sang-Ki Kim; Hyun-Young Kim; Seung-Hwan Lee; Mijeong Lee; Duck Cho (PLoS ONE, 2026)
Lentiviral vectors (LVs) pseudotyped with either vesicular stomatitis virus glycoprotein (VSV-G) or baboon envelope glycoprotein (BaEV) have been studied for chimeric antigen receptor (CAR) transduction in natural killer (NK) cells. However, the stability of CAR expression and the persistence of vector genomes following transduction remain underexplored. We generated CAR-NK92 cells using either VSV-G- or BaEV-pseudotyped LVs and evaluated CAR expression kinetics, cytotoxic function, and vector DNA persistence over time. Primary expanded NK (eNK) cells were further transduced with BaEV-LVs to assess applicability in primary cells. Although VSV-G-CAR-NK92 cells transiently yielded high surface expression of CAR, this expression rapidly declined. Genomic DNA analysis revealed marked degradation of transfer DNA and reduced integration stability of VSV-G-transduced cells. BaEV-LVs, however, supported more sustained CAR expression by NK92 cells, demonstrating persistent gDNA integration and durable cytotoxicity, which were also replicated in eNK cells. In conclusion, these findings support BaEV-LVs as a preferred platform for CAR-NK cell engineering.